Perbandingan Fikih tentang Mudharabah: Analisis Keterbatasan dan Hambatan dalam Perkembangannya - Hafizd, Jefik Zulfikar; Al-Hakim, Sofian; Gojali, Dudang (EL-EMIR Institute, 2024)
Mudharabah is a unique financial instrument in the Islamic banking system, where capital from one party (shahibul maal) is managed by another party (mudharib) to generate profit, which is shared according to a pre-agreed arrangement. This study aims to analyze the concept of mudharabah from the perspective of fiqh and explore the limitations and challenges faced in its implementation in the modern Islamic banking system. Using a qualitative approach through a literature review method, this research examines various classical and contemporary texts related to the relevant fiqh principles. The results show that mudharabah is a partnership between the capital provider and the manager, with profits shared according to the agreement and losses borne by the capital provider unless due to the manager's negligence. Ibn Rusyd divides mudharabah into mudharabah muqayyadah (restricted) and mudharabah muthlaqah (unrestricted), emphasizing the risk of gharar in capital assessment. Wahbah al-Zuhaili also highlights the importance of transparency and protection for both parties in the mudharabah contract, as well as the need for flexibility in its application to align with modern economic developments. Meanwhile, the DSN MUI has issued fatwas as practical guidelines suited to Indonesia's modern financial conditions, classifying mudharabah into four forms: muqayyadah, muthlaqah, tsuna'iyyah (involving two parties), and musytarakah (combined with musharakah). The implementation of mudharabah in Bank Muamalat and Bank Syariah Indonesia shows practical applications but faces challenges such as oversight and operational risks. The main obstacles include a lack of public understanding, high operational and market risks, as well as regulatory and infrastructure limitations. Although mudharabah holds great potential as an Islamic financial instrument, these challenges need to be addressed to improve its effectiveness and application in Indonesia.